PERLINDUNGAN HUKUM TERHADAP PASIEN ATAS PENGENAAN TARIF RAPID TES ANTIGEN-SWAB DI ATAS BATASAN TERTINGGI - Iqbal Shofyan Nur (2021)
COVID-19 is a contagious disease caused by SARS CoV-2. One way to determine someone who's infected COVID-19 with rapid antigen test. The fare antigen rapid test has been set through Circular Letter. Law Number: HK.02.02/I/4611/2020 regarding the Limit of Highest Fare Rapid Antigen-Swab Test, however some hospitals violate these provisions. The problem studied is how the legal protection of patients on Fare Rapid Antigen-Swab Test above the highest limit and responsibility. The method used juridical normative through literature study, including the primary law, secondary, and tertiary. The results showed the legal protection for patients on fare Rapid Antigen-Swab Test above the highest limit, as regulated in Burgerlijk Wetboek, the Consumer Protection Laws, and the Hospital Laws, a patient can claim for compensation to hospital. However by author, these provisions haven't provided full legal protection, because society must take relatively long and complicated legal remedies and the court decision not as expected. The responsibility for hospital or health clinic should implement Circular as well and recovery or refund the overpayment of the price range specified. It needs a government role in providing pinalty against violators Circular Letter Law and charge to recovery or refund the overpayment of the price range specified. Keywords: Covid-19, Legal protection, Rapid Test Antigen, Responsibility.